ANALISIS HEAD LOSSES PADA PENSTOCK UNIT III DI PERUM JASA TIRTA II UNIT JASA PEMBANGKIT PLTA IR. H. DJUANDA - Redaksi Tim Jurnal (JURNAL POWERPLANT, 2018)
One of the power plants in the labor system is hydropower, which is a power plant by utilizing water resources as its working fluid. In the operation of the hydropower requires high reliability sothat the energy production contuinitas to the load center or to the power system network can be more optimum. One of the components in the hydropower plant is penstock. Closed pipeline, whether it is laminar or turbulent, must have head losses. Head losses on penstock is a phenomenon of losses on the penstock so as to make the head value on the hydropower becomes reduced. At Penstock unit III PLTA Ir. H. Djuanda there are two phenomenon of head losses, namely: head losses major caused by friction penstock against water and minor head losses in the form of bend 900 with radius 4.375 m and 11.3 m from the axis penstock. Temperature changes affect the size of head losses, but they do not significantly affect penstock efficiency. At a temperature of 240C and a flow rate of 5m / s obtained a total head losses of 0606 m so as to make the potential of turbine inlet power down to 31,247 MW or 99.21%.